An integrated model‐driven method for in‐treatment upper airway motion tracking using cine MRI in head and neck radiation therapy. Issue 8 (21st July 2016) - Li, Hua; Chen, Hsin‐Chen; Dolly, Steven; Li, Harold; Fischer‐Valuck, Benjamin; Victoria, James; Dempsey, James; Ruan, Su; Anastasio, Mark; Mazur, Thomas; Gach, Michael; Kashani, Rojano; et al.
Abstract : Purpose: For the first time, MRI‐guided radiation therapy systems can acquire cine images to dynamically monitor in‐treatment internal organ motion. However, the complex head and neck (H&N) structures and low‐contrast/resolution of on‐board cine MRI images make automatic motion tracking a very challenging task. In this study, the authors proposed an integrated model‐driven method to automatically track the in‐treatment motion of the H&N upper airway, a complex and highly deformable region wherein internal motion often occurs in an either voluntary or involuntary manner, from cine MRI images for the analysis of H&N motion patterns. Methods: Considering the complex H&N structures and ensuring automatic and robust upper airway motion tracking, the authors firstly built a set of linked statistical shapes (including face, face‐jaw, and face‐jaw‐palate) using principal component analysis from clinically approved contours delineated on a set of training data. The linked statistical shapes integrate explicit landmarks and implicit shape representation. Then, a hierarchical model‐fitting algorithm was developed to align the linked shapes on the first image frame of a to‐be‐tracked cine sequence and to localize the upper airway region. Finally, a multifeature level set contour propagation scheme was performed to identify the upper airway shape change, frame‐by‐frame, on the entire image sequence. The multifeature fitting energy, including the information of intensity variations, edge saliency, curve geometry, and temporal shape continuity, was minimized to capture the details of moving airway boundaries. Sagittal cine MR image sequences acquired from three H&N cancer patients were utilized to demonstrate the performance of the proposed motion tracking method. Results: The tracking accuracy was validated by comparing the results to the average of two manual delineations in 50 randomly selected cine image frames from each patient. The resulting average dice similarity coefficient (93.28%  ±  1.46%) and margin error (0.49  ±  0.12 mm) showed good agreement between the automatic and manual results. The comparison with three other deformable model‐based segmentation methods illustrated the superior shape tracking performance of the proposed method. Large interpatient variations of swallowing frequency, swallowing duration, and upper airway cross‐sectional area were observed from the testing cine image sequences. Conclusions: The proposed motion tracking method can provide accurate upper airway motion tracking results, and enable automatic and quantitative identification and analysis of in‐treatment H&N upper airway motion. By integrating explicit and implicit linked‐shape representations within a hierarchical model‐fitting process, the proposed tracking method can process complex H&N structures and low‐contrast/resolution cine MRI images. Future research will focus on the improvement of method reliability, patient motion pattern analysis for providing more information on patient‐specific prediction of structure displacements, and motion effects on dosimetry for better H&N motion management in radiation therapy.